P119. Activity-dependent plasticity of the endolymphatic space in vestibular migraine – A single case study. Issue 8 (August 2018) - Kirsch, V.; Becker-Bense, S.; Berman, A.; Kierig, E.; Ertl-Wagner, B.; Dieterich, M.
Abstract : Introduction: A new reasonable and dependable distinguishing criterion in the difficult clinical differentiation between Vestibular Migraine (VM) and Menière's Disease (MD) might be the proof of an endolymphatic hydrops (ELH) via gadolinium-enhanced magnetic resonance imaging of the inner ear (iMRI)Lempert et al. . However, so far published studies are inconclusive and sparse. This single case study clinically documents the volume of the endolymphatic space (ELS) in a VM patient longitudinally over 12 months during an attack-free period (T1), shortly after an VM attack (T2), and three attack-free months later (T3). Case report & methods: A 61-year old female patient with a 40-year history of recurrent attacks of spontaneous rotational vertigo lasting from a few hours to several days and occurring 1–4 times in 6 months was classified as definite VM. Additional symptoms during the attacks were unsteadiness, a feeling of bilateral head-fullness, bilateral aural pressure, intolerance of motion, photo- and phonophobia; no affection of hearing. Independent of these attacks, regular episodes of migraneous headache were reported. A bilateral vestibulopathy affecting the lower-frequency range had been detected earlier. Diagnostic work-up included neurootological and neuro-orthoptic assessment, VOG during caloric stimulation and head-impulse test [HIT], and audiometry. A delayed MRI of the ELS 4 h after the intravenous injection of gadobutrol was performed in a 3 T scanner (Nakada et al., 2014 ). ELH was characterized on published criteria (Baráth et al., 2014 ) whilst including an extra grade. Volumetric assessment of ELS used manual segmentation in combination with machine learning and automated local thresholding algorithms (Gürkov et al., 2015 ). Results: Our study revealed an activity-dependent plasticity of the ELS with phases of ELH grade I-II within the left (L)- and right (R)- sided vestibule (v) or cochlea (c) (T1: R/Lv/c = grade 0; T2 R/Lv = grade II, R/Lc = grade I; T3: Rv = grade II, Rc = grade I; Lv = grade I, Lc = grade I) without relevant change in the other diagnostics (HITmean gain: R/LT1 = 0.8, R/LT2 = 0.9; R/LT3 = 0.8; caloricsmean [°/s]: R/LT1 = 2, R/LT2 = 4; R/LT3 = 5; audiometrymean [dB]: R/LT1 = 15, R/LT2 = 15; R/LT3 = 15). Longitudinal (T1–T3) depiction of detailed results revealed activity-dependent plasticity of the endolymphatic space (ELS) of the right inner ear showing an endolymphatic hydrops (ELH) without relevant changes in the ipsilateral diagnostics (HIT [gain], caloric [°/s], audiometry [dB]). Discussion: This is the first time that plasticity of the ELS is described in VM dependent on the disease activity with an ELH during and after an attack. This raises further questions on the pathognomonic significance of the detection of an ELH within the cochlea and/or vestibule in Menière's Disease (MD) [2] and even more so in VM patients [4, 5].